DOAJ directory of open access journals [electronic resource] (DOAJ, 2020)
The DOAJ (Directory of Open Access Journals) was launched in 2003 at Lund University, Sweden, with 300 open access journals. Today, the independent database contains ca. 12000 open access journals covering all areas of science, technology, medicine, social science and humanities. DOAJ is a community-curated online directory that indexes and provides access to high quality, open access, peer-reviewed journals. DOAJ is independent. All funding is via donations, 18% of which comes from sponsors and 82% from members and publisher members. All DOAJ services are free of charge including being indexed in DOAJ. All data is freely available. DOAJ operates an education and outreach program across the globe, focusing on improving the quality of applications submitted.